2014
DOI: 10.1108/jfm-02-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Organising cleaning in Norwegian public FM

Abstract: 2014),"The relation between innovation sources and ICT roles in facility management organizations", Access to this document was granted through an Emerald subscription provided by emerald-srm:448207 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The way a service is organised can also be influenced by building type, e.g., whether outsourcing or own in-house production is the main supply model and/or to what degree it is a supporting supply model (Klungseth, 2014). As an example, a main supply model can be in-house service supply, concurrently it is possible for the organisation to add outsourcing as a supporting service supply to allow more flexibility in the service delivery.…”
Section: Service-buildingmentioning
confidence: 99%
“…The way a service is organised can also be influenced by building type, e.g., whether outsourcing or own in-house production is the main supply model and/or to what degree it is a supporting supply model (Klungseth, 2014). As an example, a main supply model can be in-house service supply, concurrently it is possible for the organisation to add outsourcing as a supporting service supply to allow more flexibility in the service delivery.…”
Section: Service-buildingmentioning
confidence: 99%
“…They suggested that it would result in lower user dissatisfaction with FM services. Literature on user satisfaction with FM services in the United States and Canada, found the in-house strategy as a strategy that yielded lower satisfaction for cleaning services in buildings (Haugen and Klungseth, 2017; Klungseth, 2014). Subsequently, empirical studies showed that the in-house sourcing strategy in itself is inadequate at certain times and due to that, many modern organisations use a mixed strategy to attain higher satisfaction for users (Haugen and Klungseth, 2017; Nardelli and Rajala, 2018; Nardelli, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Redlein and Zobl (2014) and Guizzi et al (2012) further highlighted that the in-house approach to FM has a poor definition of the scope of work, and roles and is less innovative in terms of defining responsibilities and can result in user dissatisfaction. Though some studies on user satisfaction with cleaning services showed that the use of in-house services yields low satisfaction in both America and Canada (IFMA Foundation, 2001; Klungseth, 2014), others have recommended the approach as the best for cleaning services (Klungseth, 2014; Redlein and Zobl, 2014). In university buildings, in-house FM was found to contribute to energy efficiency and user satisfaction more than outsourcing but this study was limited in terms of the FM services explored (Gansmo, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%